Taking in the complete picture: Framing the use of 360-degree video for teacher education practice and research. (March 2022) - Cross, Simon; Wolfenden, Freda; Adinolfi, Lina
Abstract: 360-degree video combined with virtual reality has potential as a significant tool and field of study in teacher education. However, research to date has been fragmented and undertaken almost exclusively in high-income contexts. In response, we articulate key features of the emerging narrative that can be used to interrogate, define and guide the opportunities afforded by this technology to support improved teaching across the globe. Furthermore, we undertake a small pilot of the technology with educators in rural India as an innovative step to extend the evidence base to low-resource contexts. Highlights: Conceptual framing for use of 360-degree video to enhance teacher education practice and research. Presentation of four key dimensions: opening observation, critical distance, spatial presence, and investigative space. Successful demonstration of use and exploration of affordances in challenging, low-resource teaching context. Found to facilitate teacher agency in sharing, viewing and noticing.